Pleasing Fungus Beetles, Pseudischyrus, Tritoma, Megalodacne, Ischyrus spp. (Insecta: Coleoptera: Erotylidae) - Paul E. Skelley (EDIS)
The bright color patterns of pleasing fungus beetles never fail to attract attention, but because of their cryptic habits they are rarely seen except by the dedicated mushroom hunter and entomologists. This document is EENY-091 (originally published as DPI Entomology Circular No. 313), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 1999.